Fluid bodies and bodily fluids in premodern Europe : bodies, blood, and tears in literature, theology, and art - Barbezat, Michael D.; Scott, Anne M. (Leeds : Arc Humanities Press, 2019)
For medieval and early modern thinkers, the apparent solidity of the body only came about through the dynamic interplay of a host of fluidities in constant flux. This interdisciplinary collection of essays, containing chapters from specialists in history, art history, medical history, and literature, examines how the intimately familiar language of the body served as a convenient medium through which to imagine and describe transformations of the larger world, both for the better and also for the worse. Its individual contributors demonstrate the myriad ways in which rethinking the human body was one way to approach rethinking the social, political, and religious realities of the world from the Middle Ages until the early modern period
Introduction : bodies, fluidity, and change / Michael David Barbezat and Anne M. Scott -- Where did Margery Kempe cry? / Anthony Bale -- Elusive tears : lamentation and impassivity in fifteenth- century passion iconography / Hugh Hudson -- Catherine's tears : diplomatic corporeality, affective performance, and gender at the sixteenth-century French court / Susan Broomhall -- Piers Plowman and the blood of brotherhood / Anne M. Scott -- Performative asceticism and exemplary effluvia : blood, tears, and rapture in fourteenth-century German Dominican literature / Samuel Baudinette -- "Bloody business:" passions and regulation of sanguinity in William Shakespeare's Macbeth and King Lear / Karin Sellberg -- Saintly blood : absence, presence, and the alter Christus / Diana Hiller -- The treatment of the body in anatomy lesson of Dr. Nicolaes Tulp / Helen Gramotnev -- Augustine on the flesh of the resurrection body in the De fide et symbolo : origen, Manichaeism, and Augustine's developing thought regarding human physical perfection / Michael David Barbezat
Includes bibliographical references and index
Print version record
JSTOR
Keywords: Human body -- Religious aspects; Human figure in art; Human body in literature; Human body -- Symbolic aspects -- Europe -- History -- To 1500.; Human beings in art; Corps humain -- Aspect religieux; Corps humain dans l'art.; Corps humain dans la littérature.; Corps humain dans l'art -- Technique; HISTORY -- Renaissance; Human body in literature; Human body -- Religious aspects; Human body -- Symbolic aspects; Human figure in art; Europe; To 1500; History